Case report: Blindness associated with Learedius learedi trematode infection in a green sea turtle, Chelonia mydas, of the northern Red Sea - Morick, Danny; Bachmann, Vanessa M.; Shemesh, Eli; Botero-Anug, Ana Maria; Zemach-Shamir, Ziv; Aizenberg, Zahi; Davidovich, Nadav; Goldberg, Daphne W.; Kan, Gaston; Ofri, Ron; Tchernov, Dan; Levy, Yaniv (Frontiers in Veterinary Science, 2023)
Spirorchiid blood flukes are widespread in sea turtles, causing disease and mortality in their populations, with high prevalence in several ocean basins. Apart from being the leading parasitic causes of sea turtle strandings in several parts of the world, these infectious agents can cause endocarditis, vasculitis, thrombosis, miliary egg granulomas, and aneurysm, which ultimately may compromise the survival of green sea turtles. More severe cases may also result in multifocal granulomatous meningitis or pneumonia, both of which can be fatal. Herein we report the first green sea turtle's case of severe trematode infection Learedius learedi in the northern Red Sea associated with bilateral blindness. Necropsy revealed multiple granulomas with intralesional trematode eggs in the optic nerve, eyes, spleen, myocardium, and lungs. The parasite was identified as Learedius learedi through specific primers of the ribosomal genome and COI sequences obtained from GenBank. Altogether, these findings emphasize the importance of recognizing the systemic nature of this particular fluke infection, in order to ultimately protect the life of these marine animals and ensure the sustainability of these species in the wild.